COLLECTIVE HEALTH AND HOSPITAL PSYCHOLOGY: COLLABORATIVE PRACTICES AIMED AT COMPREHENSIVE HEALTH CARE - Belancieri, Maria de Fatima (Seven Editora, 2025)
This text approaches, in a reflective and critical way, the insertion of Hospital Psychology in the logic of Collective Health, considering the transformations in the care model and the centrality of the subject in its biopsychosocial complexity, also highlighting the collaborative and interdisciplinary practices that promote the integrality of care in the Unified Health System.  Hospital Psychology is presented as an essential area to understand and intervene in the biopsychosocial aspects of illness, hospitalization and palliative care, working with patients, family members and multiprofessional teams.  It differs from Clinical Psychology and Health Psychology by its focus on the hospital context and articulation with other areas of health. Interdisciplinary action, involving professionals such as nurses, physiotherapists and nutritionists, is emphasized as fundamental for humanized and patient-centered care.  In addition, the text discusses the impact of the hospital environment on the mental illness of health professionals, proposing strategies to promote resilience and mental health.  Finally, it reinforces the importance of ethical and political practices that value subjectivity, humanization and comprehensiveness in care, aligned with the principles of the SUS in the hospital context.DOI: https://doi.org/10.56238/sevened2025.018-017